The Effects of Employees’ Satisfaction and Leadership Styles on Organizational Performance: Organizational Commitment as a Dual Mediator - Lee, Yu-Je; Lee , I-Chao; Lin, Chin-Lang (Asian Journal of Empirical Research, 2014)
This study aims to explore the effects of employees’ satisfaction and leadership styles with organizational commitment as the dual mediator on organizational performances of IC design houses listed in Taiwan. The research subjects are the managers and directors of the IC design houses listed in Taiwan. Simple random sampling is adopted. Meanwhile, this study performs Structural Equation Modeling (SEM) to validate the model fit and the imitative effect between the structural model and the measurement model. The next step is to run the Sobel Test, Bootstrapping, and Mackinnon PRODCLIN2 to test the dual mediating effect. The results suggest that in the IC design houses listed in Taiwan, (1) employees’ satisfaction has positive and significant influence on organizational commitment; (2) employees’ satisfaction has direct, positive and significant influence on organizational performances; (3) organizational commitment has significant influence on organizational performances; (4) leadership styles have positive and significant influence on organizational commitment; and (5) leadership styles have positive and significant influence on organizational performances. These findings in part speak of the dual mediating effect from organizational commitment. They also imply that organizational commitment plays a pivotal role in the promotion of organizational performances, although organizational commitment is by no means the only factor. It is also necessary to address other issues so as to improve organizational performances.